Tìm x, biết:
\(x-3\frac{1}{2}:x=\frac{-20}{7}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1:
a) \(x-\frac{20}{11.13}-\frac{20}{13.15}-...-\frac{20}{53.55}=\frac{3}{11}\)
\(x-\left(\frac{20}{11.13}+\frac{20}{13.15}+...+\frac{20}{53.55}\right)=\frac{3}{11}\)
\(x-\frac{20}{2}.\left(\frac{1}{11}-\frac{1}{13}+\frac{1}{13}-\frac{1}{15}+...+\frac{1}{53}-\frac{1}{55}\right)=\frac{3}{11}\)
\(x-10.\left(\frac{1}{11}-\frac{1}{55}\right)=\frac{3}{11}\)
\(x-10\cdot\frac{4}{55}=\frac{3}{11}\)
\(x-\frac{8}{11}=\frac{3}{11}\)
\(x=1\)
b) \(\frac{1}{21}+\frac{1}{28}+\frac{1}{36}+...+\frac{2}{x.\left(x+1\right)}=\frac{2}{9}\)
\(\frac{2}{42}+\frac{2}{56}+\frac{2}{72}+...+\frac{2}{x.\left(x+1\right)}=\frac{2}{9}\)
\(\frac{2}{6.7}+\frac{2}{7.8}+\frac{2}{8.9}+...+\frac{2}{x.\left(x+1\right)}=\frac{2}{9}\)
\(2.\left(\frac{1}{6}-\frac{1}{7}+\frac{1}{7}-\frac{1}{8}+\frac{1}{8}-\frac{1}{9}+...+\frac{1}{x}-\frac{1}{x+1}\right)=\frac{2}{9}\)
\(2.\left(\frac{1}{6}-\frac{1}{x+1}\right)=\frac{2}{9}\)
\(\frac{1}{6}-\frac{1}{x+1}=\frac{1}{9}\)
\(\frac{1}{x+1}=\frac{1}{18}\)
=> x + 1 =18
x = 17
bài 2 ko bk lm, xl nha
a) \(\frac{x+3}{-4}=\frac{5}{20}\)
\(\frac{-\left(x+3\right)}{4}=\frac{1}{4}\)
- x - 3 = 1
- x = 1 + 3
- x = 4
x = - 4
b) \(\frac{2x+3}{7}=\frac{x-1}{15}\)
15.(2x + 3) = 7.(x - 1)
30x + 45 = 7x - 7
30x - 7x = - 7 - 45
23x = - 38
x = \(\frac{-38}{23}\)
Ta có: \(\frac{3-x}{x+2}=\frac{7-x}{x+20}\Rightarrow\left(3-x\right).\left(x+20\right)=\left(x+2\right).\left(7-x\right).\)
Ta có : \(\frac{x+1}{5}=\frac{x+2}{6}\)
\(\Rightarrow\left(x+1\right)6=5\left(x+2\right)\)
\(\Leftrightarrow6x+6=5x+10\)
\(\Leftrightarrow6x-5x=10-6\)
\(\Rightarrow x=4\)
\(\frac{x+1}{2}\)= \(\frac{8}{x+1}\)
x + 1 . x + 1 = 2 . 8
x . 2 = 16
x = 16 : 2
x = 8
\(x-3\frac{1}{2}:x=-\frac{20}{7}\)
\(x-\frac{7}{2}:x=-\frac{20}{7}\)
\(x:x=-\frac{20}{7}+\frac{7}{2}\)
\(x=-\frac{40}{14}+\frac{49}{14}\)
\(x=\frac{9}{14}\)
Vậy \(x=\frac{9}{14}\)